2015
DOI: 10.5152/tud.2015.40336
|View full text |Cite
|
Sign up to set email alerts
|

The transrectal single port laparoscopic radical prostatectomy in a cadaver model

Abstract: Objective: To explore the feasibility of laparoscopic trans-rectal Natural Orifice Transluminal Endoscopic Surgery (NOTES) radical prostatectomy in a cadaveric model and to define anatomical landmarks of this surgical route. Material and methods:After the ethical clearance, the study was conducted in Turkish Council of Forensic Medicine. With the cadaver in an exaggerated lithotomy position, a full thickness incision was made on the anterior wall of the rectum. The anteriorly visible Denonvilliers' fascia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Coloshield may serve as an effective colon occlusion device during transrectal NOTES. It may contribute towards development of transrectal hybrid-NOTES in abdominal organs that are remote from the rectum such as cholecystectomy [7], prostatectomy [22], nephrectomy [23,24], or right sided colectomy [25]. Rectal washout with povidone reduced the contamination of the rectal wall and peritoneum in left colic resection (10).…”
Section: Discussionmentioning
confidence: 99%
“…Coloshield may serve as an effective colon occlusion device during transrectal NOTES. It may contribute towards development of transrectal hybrid-NOTES in abdominal organs that are remote from the rectum such as cholecystectomy [7], prostatectomy [22], nephrectomy [23,24], or right sided colectomy [25]. Rectal washout with povidone reduced the contamination of the rectal wall and peritoneum in left colic resection (10).…”
Section: Discussionmentioning
confidence: 99%
“…Akça et al[19] described transrectal NOTES prostatectomy in a cadaveric model. The cadaver was placed in an exaggerated lithotomy position, the anterior rectal wall was incised, and a single port device (GelPOINT ® , Applied Medical, Santa Margarita, CA, United States) was deployed, through which all working and camera ports were inserted through.…”
Section: Transrectal Urologic Notesmentioning
confidence: 99%
“…The cadaver was placed in an exaggerated lithotomy position, the anterior rectal wall was incised, and a single port device (GelPOINT ® , Applied Medical, Santa Margarita, CA, United States) was deployed, through which all working and camera ports were inserted through. The authors reported ease of exposure of the posterior surface of the prostate and seminal vesicles with intact specimen extraction, and pointed the way for further testing with respect to feasibility of lymph node dissection using the transrectal route[19]. …”
Section: Transrectal Urologic Notesmentioning
confidence: 99%
“…The desire for reproducible, minimally invasive surgery, which reduces complication rates and maximizes cosmetic outcomes, is met by natural orifice transluminal endoscopic surgery (NOTES). [1] Akça et al [2] revealed that radical prostatectomy may be performed using a transrectal NOTES route. The authors state that transrectal radical prostatectomy is technically feasible in the cadaver model and the transrectal NOTES route provides good exposure and easy access to the posterior surface of the prostate.…”
mentioning
confidence: 99%
“…This technique has the same advantages as transrectal NOTES radical prostatectomy, such as minimal invasiviness and improved cosmetic outcomes, with the lack of potential risks seen rectal injury. Nevertheless, the study by Akça et al [2] is noteworthy, important, and will guide researchers in finding the best type of approach for radical prostatectomy surgery.…”
mentioning
confidence: 99%